Comparison of the clinical performance of OmniPlex‐HPV and GeneFinder HPV for the detection and genotyping of human papillomaviruses in cervical specimens. Issue 9 (September 2018) - Hong, GeeHay; Park, Yun Guk; Jin, Han Wool; Choi, Sam Kyu; Chi, Hyun Young; Cho, Woo Jae; Lee, Joo Hee; Han, Sol; Hong, Sun Pyo
Abstract : Purpose. : Human papillomavirus (HPV) infection in women is known to promote the development of cervical neoplasia. Specific HPV genotypes are more highly associated with disease, and therefore detection and genotyping of HPV infection is critical for preventing and effectively treating cervical cancer. Consequently, various assays using diverse technologies have been developed to detect HPV genotype. Recently the OmniPlex‐HPV and GeneFinder HPV methods, based on PCR and Luminex xMAP liquid bead microarray technologies, were developed for the detection of 40 and 32 HPV genotypes, respectively. The purpose of this study was to compare the clinical performance of OmniPlex‐HPV and GeneFinder HPV. Methodology. : The study included 300 cytology‐confirmed cervical swab specimens. In cases where there was a discrepancy between the two assay results, type‐specific direct sequencing was performed. Result. : We found a high overall agreement between OmniPlex‐HPV and GeneFinder HPV for detecting the presence or absence of high‐risk HPV (HR HPV) (90.7 %, κ=0.810). However, OmniPlex‐HPV showed greater sensitivity than GeneFinder HPV in the identification of multiple genotype‐infected samples. Specifically, diagnostic sensitivities for HR HPV positivity in high‐grade squamous intra‐epithelial lesions (HSIL) were 100.0 % for OmniPlex‐HPV and 96.8 % for GeneFinder HPV. Conclusions. : Our results suggest that OmniPlex‐HPV and GeneFinder HPV are highly comparable for the detection and genotyping of HPV, but OmniPlex‐HPV displays greater accuracy in cases of multiple HPV infection.